MODEL PERENCANAAN PENGGUNAAN DANA CUKAI TEMBAKAU DAN DAMPAKNYA PADA KESEJAHTERAAN PETANI - Sondayani, Elis (Unversitas Prof. Dr. Moestopo (Beragama), 2024)
The management of Tobacco Excise Revenue Sharing Funds (DBH CHT) plays a strategic role in supporting regional economic improvement, particularly for communities dependent on the tobacco agricultural sector. Evaluating the planning and implementation processes of fund usage, as well as how these funds contribute to maintaining labor sustainability and enhancing the welfare of tobacco farmers, is crucial. This study aims to analyze the planning model for the use of DBH CHT in West Java Province and its impact on the welfare of tobacco farmers, as well as to identify factors influencing the effectiveness of planning. The research employs qualitative methods with a case study approach in several areas of West Java. Data collection was conducted through interviews with tobacco farmers, local officials, and document analysis related to DBH CHT. The results indicate that the planning model for DBH CHT in West Java aligns with regulations but still faces challenges in budget absorption, particularly in the areas of community welfare and law enforcement. Despite efforts to improve farmers' welfare, the tangible impact on income and welfare still needs enhancement. This is influenced by factors such as less than optimal coordination between local government agencies (OPD) and relevant ministries, limitations in beneficiary data, and the need for increased transparency and accountability in fund management. This study provides policy recommendations to enhance the effectiveness of DBH CHT planning, especially in supporting the welfare of tobacco farmers in West Java.